DEVELOPMENT OF AN ELECTROSTATIC DISCHARGE (ESD) EVENT DETECTOR SYSTEM FOR AN ELECTRONIC MANUFACTURING PRODUCTION LINE - AHMAD SHAKARIA, AHMAD FARIS ASLAM (IRC, 2020)
An electrostatic discharge (ESD) event detector system, known as Electromagnetic Interference (EMI), was developed for an electronic manufacturing production line based on strength system to detect an ESD event and determine the efficiency of ESD prevention measures. The detector is composed of two EMI detectors estimates an ESD event and localizes the event using an enhanced trilateration method. The EMI detector was built using Arduino with data transfer by wireless module. Stationary nodes provide reference positions, with mobile nodes equipped with an EMI detector used throughout the production line to detect ESD event. The evaluation results indicate the detector worked well and that ESD event can be detected. The data was subsequently used for an ESD control program.